Geology, petrography and geochemistry of the association trondhjemite-tonalite-granodiorite (TTG) of the eastern end of the Transition Subdomain, Carajás Province, Pará - Santos, Patrick Araujo dos; Teixeira, Mayara Fraeda Barbosa; Dall’Agnol, Roberto; Guimarães, Fabriciana Vieira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
A tonalite-trondhjemite-granodiorite (TTG) suite is the main unit of the easternmost area of the Transition Subdomain of the Carajás Province. Trondhjemites and tonalites are dominants, with subordinate granodiorites, all containing biotite and magmatic epidote as main mafic minerals. The trondhjemites and tonalites show petrographic and geochemical characteristics similar to that of Archean TTG suites, while the granodiorites displays a calc-alkaline trend and are enriched in K2O, Rb and Ba, when compared to the dominant trondhjemites. The geochemical data apparently rule out a link between trondhjemites and granodiorites by fractional crystallisation or partial melting of the TTG. The tonalites and trondhjemites have affinities with TTG with high La/Yb and Sr/Y ratios of the Carajás province. This suggests a garnet amphibolite source, formation of the magma at high pressure (ca. 1.5 GPa) and magmatic evolution controlled by the fractionation of garnet and possibly amphibole. Plagioclase was probably absent in the source and was not a relevant fractionating phase. The wide occurrence of TTG in the mapped area indicates that these rocks are abundant in the Transition Subdomain, reinforcing the hypothesis that this region may represent an extension of the Rio Maria domain reworked during the Neoarchean.
Keywords: Trondhjemite; Granodiorite; TTG; Archean; Transition Subdomain